Energy Security of Territories as a Factor of Sustainable Development under the Conditions of Economic Changes - Kapitonov, Ivan A.; Voloshin, Vladimir I.; Korolev, Vitaly G. (International Journal of Energy Economics and Policy, 2019)
Territorial security implies the possibility of providing a continuous process of development and functioning in a particular locality. Taking into account that fact that the main focus is now made on the complex development of territories, the continuous improvement of the mechanisms ensuring the process is constantly being improved. The article discusses how it is possible to use the method of mathematical modeling and statistical evaluation in order to answer the question whether there are enough resources in the territory in order the development to be continuous. The urgency of the research is determined by the fact that the most important element of development is the possibility of consuming energy resources and, accordingly, the possibility of their production in conditions of economic change. The novelty of the research is determined by the fact that for the first time the question is raised about the structure of the energy security of the territory. The authors consider the issue of compliance with the structure of energy consumption as an object of research and propose to calculate the level of energy security by the extent possible to provide the territory independently, if necessary, at the expense of alternative energy sources. The practical direction of the research is determined by the fact that the possibility of independent development of territories is projected without external influence from agents of economic development. The paper analyzes not only the existing system of today, but also the forecasting model. Keywords: Development, Power Industry (Energetics), Security, Territory JEL Classifications: O10, O13, N7 DOI: https://doi.org/10.32479/ijeep.8273